Implications of Technological Evolution on Human Resource Management Strategies and Legal Compliance - Yuspika Yuliana Purba (Jurnal Minfo Polgan, 2023)
Technological evolution, particularly in the realms of digitization and automation, has had a profound impact on how companies conduct their business. The use of artificial intelligence systems, data analytics, and collaborative platforms has transformed work processes and expedited business operations. This research aims to analyze the implications of technological evolution on human resource management strategies and legal compliance. The study utilizes a comprehensive analysis of previously published literature, employing a qualitative analysis approach to gain a thorough understanding of the issues at hand. The research period spans from 2000 to 2023. The study's findings indicate that technological evolution has significantly affected human resource management strategies and legal compliance, especially within the context of Indonesia's Law Number 13 of 2003 concerning Manpower. The integration of technology into human resource management processes has enhanced efficiency and productivity but has also posed new challenges related to employee privacy, data protection, and changes in work dynamics.